2022
DOI: 10.1371/journal.pone.0274290
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and physical frailty among older Mexican Americans: Findings from an 18-year follow up

Abstract: Purposes The relationship between body mass index (BMI) and frailty in older Mexican Americans has not been previously studied. The objective of this study was to examine the relationship between BMI and frailty among non-frail older Mexican Americans at baseline over 18 years of follow up. Methods Longitudinal population-based study of 1,648 non-institutionalized Mexican Americans aged ≥ 67 years from the Hispanic Established Population for the Epidemiologic Study of the Elderly (1995/96-2012/13). Frailty p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…The findings of this study are similar to those found in the longitudinal study of the WHAS, the ELSA, the National Health and Aging Trends Study, and the Toledo Study for Healthy Aging, all of which found that older adults with VI had greater odds of developing frailty (Gonzales-Turín et al, 2021;Hou et al, 2022;Liljas et al, 2017;Swenor, Lee, Tian, et al, 2020). Participants who were overweight had lower odds of frailty, although prior research has shown overweight to be associated with frailty (Rutherford et al, 2022;Strandberg et al, 2012;Yuan et al, 2021). In addition, hypertension was associated with greater odds of frailty in previous studies (Vetrano et al, 2018); however, in this study, participants who reported hypertension had lower odds of frailty.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings of this study are similar to those found in the longitudinal study of the WHAS, the ELSA, the National Health and Aging Trends Study, and the Toledo Study for Healthy Aging, all of which found that older adults with VI had greater odds of developing frailty (Gonzales-Turín et al, 2021;Hou et al, 2022;Liljas et al, 2017;Swenor, Lee, Tian, et al, 2020). Participants who were overweight had lower odds of frailty, although prior research has shown overweight to be associated with frailty (Rutherford et al, 2022;Strandberg et al, 2012;Yuan et al, 2021). In addition, hypertension was associated with greater odds of frailty in previous studies (Vetrano et al, 2018); however, in this study, participants who reported hypertension had lower odds of frailty.…”
Section: Discussionsupporting
confidence: 82%
“…Covariates. Specific covariates were included in the analysis as they have been reported to be associated with VI and frailty (Afunugo et al, 2023;Court et al, 2014;Ehrlich et al, 2021;Garin et al, 2014;Ong et al, 2018;Rutherford et al, 2022;Shukla & Tripathy, 2023;Swenor et al, 2015;Ventura et al, 2023;Vetrano et al, 2018;Welch et al, 2021;Zheng et al, 2018). Covariates included socio-demographic variables (age, sex, marital status, years of education, financial strain, nativity status, language of interview, social isolation [lives with family vs. alone]), BMI, current smoking status, comorbidities (hypertension, arthritis, cancer, diabetes, heart attack, hip fracture, and stroke), hearing impairment, depressive symptoms using the CES-D (Radloff, 1977), and cognitive function assessed with the MMSE (Folstein et al, 1975).…”
Section: Methodsmentioning
confidence: 99%
“…16,18 One 2022 study showed greater odds of frailty in participants who had a BMI of 35 or greater, with lower odds in those with a BMI between 25 and 34. 67 Others showed this association with a BMI of 30 or greater or just in women (and not men). [68][69][70][71] Additionally, the Women's Health Initiative Observational Study in 2005 found participants who were underweight had a higher hazard ratio of being frail.…”
Section: Discussionmentioning
confidence: 95%
“…72,73 Among individuals who are underweight, frailty may be related to decreased muscle mass and lack of nutrition. 67,73,74 Whereas, in the obese group, the frailty association is thought to be related to co-morbidities, such as diabetes and cardiovascular disease, which are frequently found with obesity. 67 Another factor adding to this complex relationship between BMI and frailty may be related to increased inflammation leading to decreased muscle mass and sarcopenic obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation